Powerful Places in the Ancient Andes - Swenson, Edward; Jennings, Justin (Book collections on Project MUSE., 2018)
"Andean peoples recognize places as neither sacred nor profane, but rather in terms of the power they emanate and the identities they materialize and reproduce. This book argues that a careful consideration of Andean conceptions of powerful places is critical not only to understanding Andean political and religious history but to rethinking sociological theories on landscapes more generally. The contributors evaluate ethnographic and ethnohistoric analogies against the material record to illuminate the ways landscapes were experienced and politicized over the last three thousand years"--